Remote supervision and control based on wireless technology to operation of central pivot irrigation machine (2018)
The availability of water resources in agriculture is a growing concern throughout the planet. The new technologies of automation and communications offer a set of solutions for the collection and analysis of information that make possible the decision making in the modern systems of agricultural irrigation. Important steps have been taken in the automa - tion of irrigation systems, focused on the adequate determination of water requirements in crops, which has a positive effect on the saving of energy carriers, water resources, and agricultural productivity. In the present research we propose to perform a real-time control and monitoring system, allowing the operation and remote monitoring of irrigation machines of center pivot. For this, a programmable logic controller and wireless communication technology are used, according with the requirements and characteristics of the context of agricultural application.